THE SPIRITUAL BIOPSYCHOSOCIALS IN SOCIAL PROTECTION ON JUVENILE DELINQUENCY - Yuningsih, Yuyun; Voo, Peter; Sumardani, Sumardani (Journal Sampurasun : Interdisciplinary Studies for Cultural Heritage, 2020)
The long-term goal of this research is to develop a method of dealing with social problems on juvenile delinquency with a Biopsychosocial - spiritual method as a way to restore the functioning of children affected by legal issues that are being fostered in Class II Sukamiskin Prison. Social protection for juvenile deliquency through various forms of service with an emphasis on aspects of spiritual biopsychosocial is in the best interest of juvenile deliquency in terms of protection in the form of social assistance, social insurance, and empowerment. Even though the child is in custody, but they are also entitled to various kinds of protection and guarantees like other normal children, such as access to education, health, spiritual services, socialization and participating in various other skills and extracurricular activities. All aspects of social protection must support a child’s biopsychosocial spiritual needs. Sukamiskin’s class II rehabilitation institution which has the authority in the delivery of services to juvenile deliquency must also cooperate with other institutions in providing social protection efforts. The specific target of this research is to provide the best social service efforts for children in order to fulfill children’s rights.